2007
DOI: 10.1111/j.1468-8123.2007.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

The timescale and mechanisms of fault sealing and water‐rock interaction after an earthquake

Abstract: Hydrogeochemical monitoring of a basalt-hosted aquifer, which contains Ice Age meteoric water and is situated at 1220 m below sea level in the Tjö rnes Fracture Zone, northern Iceland, has been ongoing since July 2002. Based on hydrogeochemical changes following an earthquake of magnitude (M w ) 5.8 on 16 September 2002, we constrained the timescales of post-seismic fault sealing and water-rock interaction. We interpret that the earthquake ruptured a hydrological barrier, permitting a rapid influx of chemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 51 publications
(116 reference statements)
6
100
3
Order By: Relevance
“…The faults in the upflow zones are already partially open and probably mechanically weak. Pulses of overpressured fluids from the crystalline basement can move upwards along these faults during coseismic permeability enhancement, temporarily changing the fluid temperature and chemistry in the sedimentary basins as observed by Claesson et al [2004, 2007]. Notably, our numerical simulations as well as geological observations suggest an upflow zone of hot hydrothermal fluids in the vicinity of Húsavik.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The faults in the upflow zones are already partially open and probably mechanically weak. Pulses of overpressured fluids from the crystalline basement can move upwards along these faults during coseismic permeability enhancement, temporarily changing the fluid temperature and chemistry in the sedimentary basins as observed by Claesson et al [2004, 2007]. Notably, our numerical simulations as well as geological observations suggest an upflow zone of hot hydrothermal fluids in the vicinity of Húsavik.…”
Section: Discussionsupporting
confidence: 54%
“…If the flow system is disturbed during a seismic event such that the two fluid reservoirs begin to communicate, mixing of shallow and deep fluids is probable. This was proposed for the TFZ by Claesson et al [2004, 2007] who provided hydrogeochemical evidence of deep fluids rising to 1 km depth near the town of Húsavik immediately after a 5.8 M earthquake which occurred in September 2002 in the TFZ.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The emergence of springs and the vast quantity of liquefied sand and silt carried to the ground surface after the earthquakes are indicators of the subsurface change to the aquifer system. Studies elsewhere have suggested that the impacts of earthquakes on hydrogeological systems may be relatively short-lived (e.g., Geballe et al 2011) although effects may last many months to a few years or more (e.g., Elkhoury et al 2006;Claesson et al 2007;Kitagawa et al 2007;Manga & Rowland 2009;Rudolph & Manga 2010;Wang et al 2012). The multiple earthquake responses recorded by DL/545 at Clyde appear to have groundwater-level offset and recovery times in the order of 200Á 300 d. At this stage, one year after the M W 7.1 Darfield earthquake, it is difficult to know the extent to which the hydrological impacts of the Canterbury earthquakes will be significant and/or long-term, although the preliminary eigen modelling motivates the hypothesis that there are certainly places in the near-field region experiencing significant longer term changes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on equations from Crank (1975) and diffusion constants from Cole and Ohmoto (1986), muscovite grains would have to have been in isotopic equilibrium with the >300 o C fluid for at least one million years in order for the oxygen and hydrogen stable isotopic compositions to be overprinted. This would mean that the fault structures remained open to heated fluids for at least one million years, which is unlikely, as faults generally seal immediately after rupture (Claesson et al, 2007;Kame et al, 2014).…”
mentioning
confidence: 99%